Descriptions of the adult male, prepupa and pupa of Xylococcus castanopsis Wu & Huang (Hemiptera: Coccomorpha: Xylococcidae) - Wu, San’an; Huang, Shaobin; Dong, Qingang (Zootaxa, 2018)
The morphologies of the adult male, prepupa and pupa of Xylococcus castanopsis Wu & Huang (Hemiptera: Xylococcidae) are described and illustrated. These developmental stages were collected at Tianluhu Forest Park, Guangzhou city, Guangdong Province, China, from the same forest stands as the holotype female.